Evaluating the potential of indigenous Rhizobacteria as biofertilizer and biopesticide against Rhizoctonia solani - MAIMUNA NONTJI; AMRAN MUIS; NURMI NONCI; NURJANNAH NONCI; FARIZAH DHAIVINA AMRAN (Smujo International, 2019)
Abstract. Nontji M, Muis A, Nonci N, Nonci N, Amran FD. 2019. Evaluating the potential of indigenous Rhizobacteria as biofertilizer and biopesticide against Rhizoctonia solani. Nusantara Bioscience 11: 79-83. Rhizobacteria are living in area of plant roots, some of them are potential as biofertilizers and biopesticides agents. This study aims to evaluate the potential of 10 isolates indigenous rhizobacteria as biofertilizer and biopesticide against banded leaf and sheath blight disease on corn. The potential of biofertilizer was evaluated by ability fixing nitrogen in Burk’s N free medium, dissolving phosphate and producing Indole Acetic Acid (IAA) hormone with spectrophotometry method. The potential of biopesticide was evaluated by synergistic of analysis with double culture method. The result of study showed that the best indigenous rhizobacteria was isolated code 10. It has potential as a biofertilizer agent (0.22% for fixing nitrogen, 18.875 ppm for dissolving phosphate and producing IAA hormone 1.524 ppm). It is also having potential as biopesticide agent against Rhizoctonia solani with relative inhibition level (RIL) of 31.3%. Isolate code 10 and code 6 are able to live in synergy so that it can be recommended as biofertilizer and biopesticide agent to form the consortium as a biological fertilizer.